2023
DOI: 10.1097/fjc.0000000000001437
|View full text |Cite
|
Sign up to set email alerts
|

PFKFB2 Inhibits Ferroptosis in Myocardial Ischemia/Reperfusion Injury Through Adenosine Monophosphate–Activated Protein Kinase Activation

Abstract: Six-phosphofructo-2-kinase/fructose-2, 6-bisphosphatase 2 (PFKFB2) is a key regulator of glycolytic enzyme. This study identified whether PFKFB2 can regulate myocardial ferroptosis in ischemia/reperfusion (I/R) injury. Mice myocardial (I/R) injury and H9c2 cells oxygen-glucose deprivation/reperfusion (OGD/R) models were established. PFKFB2 expression was enhanced in I/R mice and OGD/R H9c2 cells. Overexpression of PFKFB2 improves heart function in I/R mice. Overexpression of PFKFB2 inhibits I/R and OGD/R-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It has been found that H/R triggers ferroptosis of H9c2 cells [25,78,[103][104][105]. In one study, it was found that deferoxamine inhibited this process [103].…”
Section: Ischemia/reperfusion Of Cardiac Injurymentioning
confidence: 99%
“…It has been found that H/R triggers ferroptosis of H9c2 cells [25,78,[103][104][105]. In one study, it was found that deferoxamine inhibited this process [103].…”
Section: Ischemia/reperfusion Of Cardiac Injurymentioning
confidence: 99%
“…Tumor cells increase energy through glycolysis to meet the physiological demands of cell proliferation (Ozcan et al, 2020). 6-phosphofructo-2-kinase/fructose-2,6biphosphatase 2 (PFKFB2) is a regulatory molecule that controls eukaryotic glycolysis (Fu et al, 2023). Studies had found that PFKFB2 overexpression enhanced gastric cancer cell growth and glycolysis (Shen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%